2011
DOI: 10.1074/jbc.m111.262352
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nucleocapsid Protein Increases Strand Transfer Recombination by Promoting Dimeric G-quartet Formation

Abstract: A preferred site for HIV-1 recombination was identified in vivo and in vitro surrounding the beginning of the HIV-1 gag gene. This G-rich gag hotspot for recombination contains three evenly spaced G-runs that stalled reverse transcriptase. Disruption of the G-runs suppressed both the associated pausing and strand transfer in vitro. Significantly, this same gag sequence was able to fold into a G-quartet monomer, dimer, and tetramer, depending on the cations employed. The pause band at the G-run (nucleotide (nt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…However, dimerization of templates through DIS and G-quartets in gag was previously shown to stimulate strand transfer (24,44). Moreover, in the context of whole genomes, the opportunity for multiple contact points should favor dimeric over monomeric G-quartet formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, dimerization of templates through DIS and G-quartets in gag was previously shown to stimulate strand transfer (24,44). Moreover, in the context of whole genomes, the opportunity for multiple contact points should favor dimeric over monomeric G-quartet formation.…”
Section: Discussionmentioning
confidence: 99%
“…Switching by the RT-We previously showed that a major recombination hot spot in the HIV-1 gag region near DIS correlates with sequences rich in G residues that can form G-quartet structures (23,24,30). We showed enhanced strand transfer resulting from G-quartet dimer formation that holds the templates in close proximity and/or G-quartet monomer or dimer formation that increases frequency of RT RNase H by pausing the RT (Fig.…”
Section: G-quartet Structure Near the Cppt Promotes Templatementioning
confidence: 99%
See 1 more Smart Citation
“…Under the second hypothesis, which does not exclude the former, there might be a direct link between enhanced recombination rates and the formation of secondary RNA structure, because these RNA structures induce stops, stalling or delays in DNA synthesis, thus favouring strand invasion (Simon-Loriere and Holmes, 2011). Interestingly, the presence or absence of the viral chaperone nucleocapsid modulates RNA secondary structure, revealing an evolutionary role for these proteins (Negroni and Buc, 2000); this effect is related to HIV-1 nucleocapsid promoting dimeric G-quartet formation (Shen et al, 2011).…”
Section: Recombination In Rna Virusesmentioning
confidence: 99%
“…24,31,32 To investigate if these patterns could be identified with our sequence data, we determined frequencies of the bases at which nascent DNA fragments paused. Only small percentages (12%) of nascent cDNA fragments paused at homopolymer sites (3-5 bases).…”
Section: Site Preference For Pausing Of Nascent Dna Fragmentsmentioning
confidence: 99%